The Effect of Time Budget Pressure, Audit Fee, and Auditor Independence on Audit Quality (Empirical Study on Foreign-Affiliated Public Accountants in Jakarta) - Bambang Subiyanto; Tiara Pradani; Nur Asiyah (AIBPM Publisher, 2023)
This study aims to determine the effect of time budget pressure, audit fees, and auditor independence on audit quality. Quantitative data is used in this study. The data used in this study is primary data. The data was obtained by distributing questionnaires to the respondents, and the data was processed in as many as 92 questionnaires. The population in this study are auditors who work at a foreign-affiliated Public Accounting Firm (KAP) in Jakarta. The test was carried out with the help of IBM SPSS statistic 25. The findings underscore the significant impact of time budget pressure on audit quality, emphasizing that auditors' performance is intrinsically linked to their ability to manage the pressures associated with tight timelines. In contrast, audit fees were not found to substantially affect audit quality, revealing that an excessive fee structure may jeopardize auditor independence. Auditor independence emerged as a critical factor, significantly influencing audit quality. A higher level of independence among auditors corresponded with improved audit quality. This research underscores the need for careful management of time constraints and emphasizes the pivotal role of auditor independence in ensuring the integrity and reliability of audit outcomes.